English as a Lingua Franca in the Eyes of Indonesian In-service Teachers: Attitudes and Beliefs - Kusumaningputri, Reni; Khazanah, Dewianti; Setiarini, Riskia; Sampurna, Hadi (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
Based on the premise that teachers are at the forefront of global multilingual cultural awareness agencies, the research on their views toward English as a Lingua Franca (ELF) concepts is critical. This study investigated the attitudes and beliefs of 120 in-service secondary teachers toward ELF in Indonesia. It employed a mixed-method design. Research data was collected using a questionnaire and semi-structured interviews. Thematic coding analysis was used to interpret qualitative data. The results indicated teachers' positive changes in attitudes and beliefs in five ELF categories: the presence of multilingual characters and pronunciation model used in the classroom, learning goals, the roles of language and culture, and the language used in the classroom and the assessment. Challenges to welcoming the ELF perspective in classroom practices identified in the study were government policy, parental support, and individual teachers' reflection on the current position of English in the global discourse, primarily since beliefs on the superiority of native English speakers were found to be strong. This study suggests that teachers’ awareness in designing sensitive instructions and materials to welcome lingua cultural varieties would improve the understanding of transpiring changes in the global sociolinguistic landscape. Government intervention is called for to provide cheaper and more accessible materials representing English variations.